VARIASI KONSENTRASI EM4 DALAM PROSES PEMBUATAN KOMPOS LINDI - Candra Rulyana; Nurjazuli Nurjazuli; Tri Joko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Large amounts of waste require special handling to reduce negative impacts. One way to reduce the negative impact of waste generation is waste processing by adding various EM4 as decomposers. The result of organic waste processing of household is leachate compost. The purpose of this research is to know the ability to use different variation of Effective Microorganism 4 (EM4) concentration in composting process. The type of research used is experimental semu (Quasi Experiment). With the design of Time series research with the Control Time Series Design. Total volume of household waste generated at the research location is 908 liters. The composition of waste generation is 378 liters of inorganic waste and 530 liters of organic waste. The percentage of household waste generated in this research is 58% organic waste and 42% of inorganic waste. In this study the average waste generated is 1.7 liters / person. The highest temperature is in the addition of EM4 with a concentration of 4% ie 34.5⁰C. The highest average daily temperature was found in the addition of EM4 2% concentration of 30⁰C. The highest compost volume of compost produced by composter with the addition of EM4 2% concentration as much as 5.9 liters. The average daily volume of the largest compost leachate produced composter with the addition of EM4 with a concentration of 2% ie 0.19 liters / day. Compost volume at least produced composter with the addition of EM4 with a concentration of 2% is 3.5 liters. The largest percentage of waste reduction to compost on the composter with the addition of EM4 with a 2% concentration of 88.3%. Suggestions for households should process organic waste caused into leach compost because it reduces the volume of waste that should be disposed in waste disposal.